IDENTIFIKASI JENIS-JENIS MANGROVE YANG BERMANFAAT SECARA EKONOMI BAGI MASYARAKAT DI PULAU SEMBILAN DAN PULAU KAMPAI, KABUPATEN LANGKAT - Eka Sapta Prasetya Silalahi; Budi Utomo; Yunasfi Yunasfi (Program studi Kehutanan USU, 2016)
The destruction rate of mangrove in Indonesia progressively increased and the economy level , especially coastal people became higher. Therefore, it’s necessary to identify what type of mangrove that can economically profitable for society. The purpose of this research was to identify type’s of mangrove that beneficial economically to society in Kampai and Sembilan Island, knowing the utilization of mangrove that valuable in economy as well as the role and participation of people in the management and utilization of mangrove. The method that used is descriptive interviews and direct observation. The result showed the people in Kampai and Sembilan Island still have little knowledge about the mangrove, so that the people is difficult to utilize the mangrove maximally. The people of Kampai and Sembilan Island majority using mangrove from the economic side like wood for building , firewood and charcoal wood. The people use it for personal utilities. Type’s of mangrove that used in Sembilan island is Bakau (Rhizophora stylosa) and Api-api (Avicenia officialis) for building wood and firewood, while in Kampai Island type’s of mangrove that using is Bakau (Rhizophora stylosa) and Tengar (Ceriops tagal) for building wood and charcoal wood.Keyword: Economic Mangrove, Kampai Island, Sembilan Island